Do you need to stop metformin in a hospitalized patient with diabetes?. Issue 11 (November 2017) - Piggott, Cleveland; Lyon, Corey
Abstract : CASE : A 54‐year‐old woman with type 2 diabetes mellitus, chronic kidney disease, and chronic obstructive pulmonary disorder (COPD) is admitted for a COPD exacerbation and a new 2L oxygen requirement. The patient weighs 90 kg; her vital signs, except for a new oxygen requirement, are normal. She is started on appropriate COPD exacerbation treatment, and during medication reconciliation, the clinician notices she takes metformin 1, 000 mg BID for her well‐controlled diabetes. Her serum creatinine is 1.5 mg/dL today, the same as 1 month before. Should she have her metformin discontinued while in the hospital?